Effect of Different Levels of Dietary Hemp Seed Powder on the Profiles of Reproductive Hormones of Awassi Ewes - Omer, Esam Saeed (American Journal of Biology and Natural Sciences, 2025)
The present study aimed to investigate the effects of Russian hemp seeds on some reproductive hormones in the Iraqi Awassi ewes. Four Awassi ewe with a mean live weight twelve local Awassi ewes between three and four years were selected (BWObserved Experimental), were grouped into three experimental groups of four ewes each of comparable body weight. Each ewe represented a unique replicate. Participants were randomly grouped into one of the three treatment conditions (Group 1 - Control - T1 which received no further supplements; Group 2 - T2 which was given the supplementation of 200mg powdered hemp seeds (in gelatin capsules) and corn flour daily; Group 3 - T3 which was given the identical supplement to T2, but a higher daily precautionary dose (300 mg). The course of treatment extended to 45 Days. The serum levels of estrogen, LH, FSH, and prolactin did not show any statistically significant differences (P>0.05) between groups. The levels of hemp seed powder used (200 and 300 mg/ewe/day) are physiologically safe for the Awassi ewes used in this study based on the results obtained.